(untitled) (World Bulletin of Management and Law, 2025)
This article explores the distinction between justice and revenge in the context of international criminal law. While revenge is driven by emotional impulses and retribution, justice is based on legal accountability, due process, and the protection of human rights. The study examines the role of the International Criminal Court (ICC) in prosecuting grave international crimes and preventing cycles of violence. Despite practical limitations, international justice remains essential for upholding the rule of law and global stability.